Profil Keterlaksanaan Pendampingan Penyusunan Modul Ajar Fisika Fase F di MGMP Fisika SMA Kabupaten Sukoharjo - Shofi Hikmatuz Zahroh; Sarwanto Sarwanto; Sukarmin Sukarmin; Fairusy Fitria Haryani; Elvin Yusliana Ekawati; Ahmad Fauzi; Daru Wahyuningsih; Pujayanto Pujayanto; Widha Sunarno (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2024)
Kurikulum Merdeka menuntut guru untuk memiliki kemampuan dalam mengembangkan perangkat ajar pembelajaran. Namun, hanya 5% guru dari 21 responden yang mengembangkan perangkat ajarnya sendiri. Oleh karena itu, grup riset Manajemen dan Inovasi Pembelajaran Fisika (MIPF) FKIP Universitas Sebelas Maret melaksanakan kegiatan pendampingan terhadap guru Fisika SMA Kabupaten Sukoharjo dalam menyusun modul ajar Fase F Kurikulum Merdeka. Tujuan dari kegiatan pendampingan antara lain, 1) memberikan pemahaman tentang Kurikulum Merdeka, asesmen diagnostic, dan proses penyusunan ATP dan modul ajar dan 2) melatih guru dalam menyusun modul ajar fisika fase F. Kegiatan pengabdian yang dilakukan grup riset MIPF diselenggarakan selama tiga (3) tahap dan melibatkan 33 guru Fisika SMA Kabupaten Sukoharjo selama bulan Juni-Agustus 2023. Berdasarkan hasil evaluasi, didapatkan bahwa guru fisika mendapatkan pemahaman yang lebih terkait prosedur pembuatan ATP (83,3% sangat paham), fungsi dan tujuan dari pembuatan ATP (83,3% sangat paham), hakikat modul ajar (83,3% sangat paham), komponen modul ajar (91,7% sangat paham), proses pembuatan modul ajar (91,7% sangat paham), tujuan asesmen diagnostic (83,3% sangat paham),  dan jenis tes diagostik (91,7% sangat paham). Selain mendapatkan wawasan baru, guru fisika juga telah menyusun luaran berupa 14 modul ajar yang telah direview oleh tim grup riset MIPF. The Kurikulum Merdeka requires teachers to have the ability to develop learning and teaching tools. However, according to a survey conducted on Sukoharjo Regency High School physics teachers, only 5% of teachers from 21 respondents developed their teaching tools. Apart from that, Phase F of the Kurikulum Merdeka will be implemented in the 2023 academic year. Therefore, the Physics Learning Management and Innovation (MIPF) research group at FKIP Sebelas Maret University is mentoring Sukoharjo Regency High School Physics teachers in preparing Modul Ajar for Phase F of the Kurikulum Merdek. The mentoring activities have two main goals: 1) to give teachers a better understanding of the Independent Curriculum, diagnostic tests, and the process of creating ATP and lesson plans (Modul Ajar); and 2) to train teachers in creating phase F physics lesson plans (Modul Ajar). The service activities carried out by the MIPF research group were held in three (3) stages and involved 33 Sukoharjo Regency High School physics teachers from June to August 2023. Based on the evaluation results, it was found that physics teachers gained a greater understanding regarding the procedure for making ATP (83.3% really understood), the function and purpose of making ATP (83.3% really understood), the nature of the Modul Ajar (83.3% really understood), the components of the Modul Ajar (91.7% really understood), the process of making the Modul Ajar (91.7% really understood), the purpose of the diagnostic assessment (83.3% really understood), and the type of diagnostic test (91.7% really understood). Results Apart from gaining new insights, the service activities carried out by the physics teacher have also prepared output in the form of 14 Modul Ajar, which was prepared by the teacher and has been reviewed by the MIPF research group team.